What is Mathematics: Gödel's Theorem and Around (Edition 2015) - Podnieks, Karlis (My University, 2015)
Hyper-textbook for students in mathematical logic and foundations of mathematics. Edition 2015.
Keywords: mathematical logic; Research Subject Categories::MATHEMATICS; foundations of mathematics; axiomatic set theory; first order arithmetic; Hilbert's Tenth problem; incompleteness theorems